Study of prevalence and socio-demographic determinants of pterygium in Sub Himalayan region, India - Padha, Abhishek; Koul, Prateek; Sharma, Swati (International Journal of Research in Medical Sciences, 2018)
Background: Pterygium, derived from the Greek work ‘pteryx’, meaning wing is a growth of fibrovascular tissue on the cornea and conjunctiva in the palpebral fissure. The present study was conducted to find out the prevalence and Socio-demographic determinants of pterygium in Sub Himalayan region of Himachal Pradesh, India. Methods: A cross-sectional study was conducted between the months of May-June 2018, in the outpatient department of Ophthalmology of Pt. Jawahar Lal Nehru Govt. Medical College and Hospital, Chamba, H.P, India. Among all the patients visiting the OPD in the given duration, a total of 200 patients having Pterygium were selected for the study. Detailed history of the all the patients were taken and required examination was done. Data collected was analysed with Microsoft excel software. Results: Out of the 200 patients, 59% were males and 41% were females. 70% of the total study population were seen in the age group 41-60years. In present study a total of 130 patients (65%) were outdoor workers. Left eye (40.5%) was the eye most frequently involved eye in present study, right eye (36.5%) also both the eyes were involved in 23% of study population. Nasal pterygium was seen in 93%, temporal pterygia 5.5% and double pterygium (both nasal and temporal presentation in same eye) in 1.5% patients. Grade I pterygium was seen in 43.5% patients, grade II in 40% and grade III pterygia were found in 16.5% of the study population. Conclusions: People living in high altitude regions and who work outdoors, are subjected to increased U.V. exposure. So, they must take appropriate precautions like wearing protective glasses and caps etc.